Revisiting the M-GUDS-S: Teacher Candidates’ Awareness and Acceptance of Diversity - Lorie Cook-Benjamin; Beth Walizer; Keith Dreiling (The Advocate, 2014)
Introduction: As shared in our article published in the spring 2013 issue of The Advocate Journal, schools of education are concerned about the best way to provide teacher candidates with clinical-based (also referred to as “field” in the literature) experiences that meet accreditation outcomes. In the Report of the Blue Ribbon Panel on Clinical Preparation and Partnerships for Improved Learning (NCATE, 2010), ten research-based principles created a framework for clinical-based practices.